Acute Coronary Syndrome in a Patient with Sarcoidosis: A Case Report - Murarka, Rohit; Hussain, Asraf; Regmi, Shyam Raj; Dhital, Bishnu Mani; Khan, Amir; Thapa, Sagar; Chaudhary, Ram Gobind; Yadav, Indresh; Shrestha, Roshan (Nepalese Heart Journal, 2024)
Sarcoidosis is a complex systemic disorder characterized by an increased cellular immune response and the development of non-caseating granulomas. Sarcoidosis can affect any other organ and cardiac involvement has been reported in a substantial percentage of individuals. A sound clinical evaluation is needed for rapid recognition and implementation of appropriate treatment alternatives. Chest pain is a common presenting symptom in sarcoidosis. We present here an interesting case of a 39-year-oldfemale presenting with ST elevation myocardial infarction who was managed by primary percutaneous intervention.